Water Purification with Natural Sorbents: Effect of Surface Modification with Nano-structured Particles; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Plotnikov E. V. Evgeny Vladimirovich; Martemianova I. Irina; Martemyanov D. V. Dmitry Vladimirovich; Zhuravkov S. P. Sergey Petrovich; Voronova O. A. Olesya Aleksandrovna; Korotkova E. I. Elena Ivanovna; Silnikov V. Vladimir (2015, 2015)
Title screen